2002
DOI: 10.1029/2001jd000358
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic NO emissions from forest and pasture soils: Relating laboratory studies to field measurements

Abstract: [1] During September and October 1999, dynamic chamber measurements were carried out to determine nitric oxide (NO) fluxes from a primary forest soil and an old pasture in the Brazilian Amazon basin as part of the project ''European Studies of Trace Gases and Atmospheric Chemistry as a Contribution to the Large-Scale Biosphere-Atmosphere Experiment in Amazonia'' (LBA-EUSTACH). In addition, soil samples were collected from these two sites, and laboratory experiments were conducted to determine the NO production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 57 publications
(102 reference statements)
5
89
0
Order By: Relevance
“…. The performance of the STEP process model in predicting herbage mass variation over time and herbage yield along a north-south bio-climatic gradient within the Sahel was tested along a 15-year period, and gave high correlation coefficients between model and measurements when the model was calibrated for each site (Tracol et al, 2006). Modifications brought to the first version of the model have been given in Jarlan et al (2008).…”
Section: Stepmentioning
confidence: 99%
See 3 more Smart Citations
“…. The performance of the STEP process model in predicting herbage mass variation over time and herbage yield along a north-south bio-climatic gradient within the Sahel was tested along a 15-year period, and gave high correlation coefficients between model and measurements when the model was calibrated for each site (Tracol et al, 2006). Modifications brought to the first version of the model have been given in Jarlan et al (2008).…”
Section: Stepmentioning
confidence: 99%
“…The quantity of nitrogen in the soil is derived from the quantity of carbon using the C / N ratio. A more detailed description of STEP can be found in Mougin et al (1995), Tracol et al (2006) and Jarlan et al (2008). Information such as the quantity of faecal and herbal masses are transferred as inputs to GENDEC, the litter decomposition model.…”
Section: Stepmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, forest soils may be regarded as minor sources of NO, except those forest soils in temperate regions, which receive considerable nitrogen inputs (NH 3 , HNO 3 , NH 4 + , NO 3 -) by wet and dry deposition. Recent studies found that the NO flux observed from temperate forests and rainforest soils is about 10 to 100-fold higher than that from dry arid and semiarid soils (12,15,16).…”
Section: Introductionmentioning
confidence: 97%